Addressing Gender-Based Occupational Segregation : Experimental Evidence from the Republic of Congo - Gassier, Marine; Pierotti, Rachael Susan; Rouanet, Lea Marie; Traore, Lacina (Washington, DC: World Bank, 2022)
Gender-based occupational segregation - the fact that men and women are typically concentrated in different occupations and economic sectors - contributes to gender gaps in earnings. In an experiment in the Republic of Congo, the authors examine whether addressing informational constraints around returns from male dominated sectors can encourage young women to apply for training in more profitable male-dominated sectors. There is high potential for interventions that pair information on returns and trade exposure. However, there are gender gaps in access to early opportunities, mainly relevant technical experience and network connections. Providing information on earnings is a low-cost intervention that can encourage young women to crossover to more lucrative trades, thereby reducing the gender gap in earnings.